SUPPLY CHAIN MANAGEMENT DAN KINERJA PERUSAHAAN - Rachbini, Widarto (Economic Faculty, Attahiriyah Islamic University, 2016)
The purpose of this study was to determine the influence of Supply Chain Management on the performance of the company. This study uses 165 manufacturing employees in Indonesia as a sample through www.googledocs.com. The analysis was conducted using Structural Equation Modeling (SEM) and processed using Lisrel 8.7. The research proves that information sharing, long term relations, cooperation and integration process, positively and significantly influence the company's performance. But Long Term Relations has no significantly influence on the company’s performance. Keywords: Supply chain management. Information Sharing, Long Term Relations, Cooperation, Process Integration, the company’s performance